Modernisasi Pendidikan Islam di Turki - IRVAN MUSTOFA SEMBIRING (Edu Global : Jurnal Pendidikan Islam, 2022)
This study aims to identify and analyze the modernization of Islamic education in Turkey. The method used in this study is the reference search method (literature study). This study uses a library approach. In the data collection process, researchers used reference searches (literature study). In analyzing the data, researchers used content analysis techniques (content analysis). This research shows that the defeat after defeat experienced by the Ottoman Turks made Sultan Mahmud II formulate a strategy to advance the Ottoman Empire with its main program being the issue of education. In reconstructing the rebuilding of the Ottoman Empire that was carried out by Sultan Mahmud II through an educational program, it did not reach the target he set out because through these reforms, Mustafa Kemal easily turned the Ottoman Empire into a secular socialist state. Mustafa Kemal and overhauled all the arrangements that had been built by the Ottoman Turks for centuries. Even the Turkish state abolished religion and revived Western moods in government. Although recently there have been attempts by the Turkish government to revive religion.